Data Protection and Corporate Reputation Management in the Digital Era - Gabriela Wojak; Ernest Górka; Michał Ćwiąkała; Dariusz Baran; Dariusz Reśko; Monika Wyrzykowska-Antkiewicz; Robert Marczuk; Marcin Agaciński; Daniel Zawadzki; Jan Piwnik (European Research Studies Journal, 2025)
Purpose: The purpose of this paper is to analyze the relationship between cybersecurity management, data protection, and corporate reputation in the context of digital transformation. The study aims to identify how organizations implement strategies and tools to mitigate cyber risks, comply with regulatory requirements, and build stakeholder trust. Design/methodology/approach: A quantitative research design was applied using an online diagnostic survey distributed to enterprises across various industries in Poland. The study examined organizational cybersecurity strategies, the use of technical and procedural safeguards, employee awareness, and the adoption of international standards such as ISO/IEC 27001 and ISO/IEC 27032. Findings: The research revealed that most organizations have formal cybersecurity strategies, conduct regular audits, and invest in awareness programs. However, despite high levels of preparedness, 75% of surveyed firms experienced cyber incidents, most often resulting in reputational damage and operational disruptions. Cybersecurity is increasingly perceived as an investment in long-term organizational stability rather than as a cost. Research limitations/implications: The study was limited to enterprises operating in Poland, and its findings may not fully capture international differences. Future research should explore cost–benefit analysis of cybersecurity investments and longitudinal changes in corporate resilience. Practical recommendations: The findings emphasize the need for integrating cybersecurity governance with corporate communication and crisis management. Organizations should treat data protection as a strategic asset and develop transparent disclosure mechanisms to maintain trust after cyber incidents. Originality/value: The paper offers one of the first empirical insights into the intersection of cybersecurity governance and corporate reputation in Polish enterprises, linking technical safeguards with strategic management perspectives.
Keywords: M15; L86; M14; 650; Cybersecurity management; Data protection; Data protection; Corporate reputation; Digital trust; governance